The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
The Oxford Handbook of Poverty and Child Development 2012
DOI: 10.1093/oxfordhb/9780199769100.013.0002
|View full text |Cite
|
Sign up to set email alerts
|

Economic Hardship and Its Consequences Across Generations

Abstract: Economic hardship and its consequences were examined across 3 generations of rural Midwestern families. Information from parents (G1) and adolescents (G2) from 556 families indicated that economic hardship experienced during adolescence predicted economic hardship in young adulthood, and this process was linked to developmental outcomes of the 3rd generation (G3). Five individual and family factors decreased the association between parents’ and offspring economic hardship over a 10-year period. G1 economic har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 55 publications
5
31
0
Order By: Relevance
“…It could be that disad-vantaged G2 participants could not afford to participate in extracurricular activities that would have contributed to their visibility in their peer group and that would have provided opportunities to develop social skills and opportunities to form friendship bonds with more classmates. This hypothetical developmental sequence is supported by results from Conger et al (2012), who found that parents' economic hardship has a negative impact both on children's affiliation with conventional peers and on their involvement in extracurricular activities, which ultimately affect their educational attainment and SES in adulthood. Because childhood likeability contributes to various components of G2 SES (educational attainment and economic-occupational indicators), further investigation might be valuable in terms of understanding the processes whereby early SES conditions influence social competence and other aspects of likeability and peer relations.…”
Section: Child Characteristics Influencing the Continuity Of Sesmentioning
confidence: 79%
“…It could be that disad-vantaged G2 participants could not afford to participate in extracurricular activities that would have contributed to their visibility in their peer group and that would have provided opportunities to develop social skills and opportunities to form friendship bonds with more classmates. This hypothetical developmental sequence is supported by results from Conger et al (2012), who found that parents' economic hardship has a negative impact both on children's affiliation with conventional peers and on their involvement in extracurricular activities, which ultimately affect their educational attainment and SES in adulthood. Because childhood likeability contributes to various components of G2 SES (educational attainment and economic-occupational indicators), further investigation might be valuable in terms of understanding the processes whereby early SES conditions influence social competence and other aspects of likeability and peer relations.…”
Section: Child Characteristics Influencing the Continuity Of Sesmentioning
confidence: 79%
“…Past work has shown that economic hardship is related to behavioral health problems, including psychological disorders, addictive behavior, physical health problems, and interpersonal dysfunction in adults and children (K. J. Conger et al, 2012;Sareen, Afifi, McMillan, & Asmundson, 2011). For instance, economic adversity has been linked to reduced social competence and elevated physiological markers of stress (K. E. Bolger, Patterson, Thompson, & Kupersmidt, 1995;Evans & English, 2002).…”
Section: Sociocultural Factorsmentioning
confidence: 99%
“…Lower family SES in childhood is associated with the development of temperament in children. For instance, lower parent income in adolescence predicts less positive emotionality, more negative emotionality, and less constraint (Conger et al, ). Furthermore, these traits go on to predict lower income in adulthood, which subsequently predicts a similar pattern of trait development in the next generation (Conger et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, lower parent income in adolescence predicts less positive emotionality, more negative emotionality, and less constraint (Conger et al, ). Furthermore, these traits go on to predict lower income in adulthood, which subsequently predicts a similar pattern of trait development in the next generation (Conger et al, ). Lower maternal education also predicts more irritability in children and lower parent income predicts more irritability, more fear, and less effortful control, and these relations remain stable over time (Lengua, ).…”
Section: Introductionmentioning
confidence: 99%